Prevalence of Pathological Brain Lesions in Girls with Central Precocious Puberty: Possible Overestimation? - Yoon, Jong Seo; So, Cheol Hwan; Lee, Hae Sang; Lim, Jung Sub; Hwang, Jin Soon (Journal of Korean medical science, 2018)
Brain magnetic resonance imaging (MRI) is routinely performed to identify brain lesions in girls with central precocious puberty (CPP). We aimed to investigate the prevalence and type of brain lesions among Korean girls with CPP and evaluate the need for routine brain MRI examinations. This retrospective cross-sectional study evaluated data on 3,528 girls diagnosed with CPP from April 2003 to December 2016, and identified 317 girls who underwent sellar MRI. Exclusion criteria were patients with a known brain tumor or who did not undergo brain MRI due to refusal or the decision of the pediatric endocrinologist. Normal sellar MRI findings were observed in 291 of the 317 girls (91.8%). Incidental findings were observed in 26 girls (8.2%). None of the patients had pathological brain lesions. The prevalence of intracranial lesions among girls who were generally healthy and without neurological symptoms but diagnosed with CPP was lower than that previously reported. Furthermore, none of the identified lesions required treatment. It may be prudent to reconsider the routine use of brain MRI to screen all patients with CPP, especially if they are healthy and neurologically asymptomatic, and are girls aged 6-8 years.